1996
DOI: 10.1128/jvi.70.10.6576-6588.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cellular origin and ultrastructure of membranes induced during poliovirus infection

Abstract: Poliovirus RNA replicative complexes are associated with cytoplasmic membranous structures that accumulate during viral infection. These membranes were immunoisolated by using a monoclonal antibody against the viral nonstructural protein 2C. Biochemical analysis of the isolated membranes revealed that several organelles of the host cell (lysosomes, trans-Golgi stack and trans-Golgi network, and endoplasmic reticulum) contributed to the virus-induced membranous structures. Electron microscopy of infected cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
249
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(270 citation statements)
references
References 69 publications
(99 reference statements)
17
249
1
3
Order By: Relevance
“…The positive-stranded RNA viruses encode nonstructural proteins (NSP) that cause proliferation and modification of membranes of the host secretory pathway. The membranes are thought to provide a physical framework or ''replication complex'' that concentrates the cellular and viral components required for virus replication (Bienz et al, 1987;Egger et al, 2002;Froshauer et al, 1988;Gazina et al, 2002;Magliano et al, 1998;Schlegel et al, 1996;van der Meer et al, 1998). Assembly of the replicase on membranes, rather than the cytosol, may also help viruses evade host defence pathways that monitor cells for double-stranded RNA (dsRNA) intermediates indicative of virus replication.…”
Section: Membrane Rearrangements Occurring During the Replicatiomentioning
confidence: 99%
See 2 more Smart Citations
“…The positive-stranded RNA viruses encode nonstructural proteins (NSP) that cause proliferation and modification of membranes of the host secretory pathway. The membranes are thought to provide a physical framework or ''replication complex'' that concentrates the cellular and viral components required for virus replication (Bienz et al, 1987;Egger et al, 2002;Froshauer et al, 1988;Gazina et al, 2002;Magliano et al, 1998;Schlegel et al, 1996;van der Meer et al, 1998). Assembly of the replicase on membranes, rather than the cytosol, may also help viruses evade host defence pathways that monitor cells for double-stranded RNA (dsRNA) intermediates indicative of virus replication.…”
Section: Membrane Rearrangements Occurring During the Replicatiomentioning
confidence: 99%
“…The accumulation of large numbers of densely packed membrane vesicles in the cytoplasm is characteristic of a picornavirus infection (Bienz et al, 1983(Bienz et al, , 1987Cho et al, 1994;Dales et al, 1965a;Schlegel et al, 1996;Stuart and Fogh, 1961;Suhy et al, 2000). Studies have suggested that vesicles induced by Poliovirus are derived from the ER, either from COPII-coated vesicles or from ER-derived autophagic double-membraned vacuoles (Bienz et al, 1987;Jackson et al, 2005;Rust et al, 2001;Schlegel et al, 1996;Suhy et al, 2000). However, the detection of ER, Golgi, and lysosomal markers in membranes induced at later stages of infection by Poliovirus suggests that more than one organelle may contribute membranes to the replication complex (Schlegel et al, 1996).…”
Section: Membrane Rearrangements Induced By Picornaviruses Provide Simentioning
confidence: 99%
See 1 more Smart Citation
“…Factors of the poliovirus RNA-replication complex localize to doublemembrane vesicles that are derived from the ER by the action of viral proteins 2BC and 3A by a mechanism that excludes resident host proteins (Schlegel et al, 1996;Suhy et al, 2000). Importantly, these structures contain LC3/Atg8 and are highlighted with the fluorophore monodansylcadaverine, a dye that specifically stains autophagosomes (Jackson et al, 2005).…”
Section: Virusmentioning
confidence: 99%
“…RNA synthesis of HCV occurs on membranes of the ER or on a membranous matrix designated membranous web (Moradpour et al, 2003) or lipid raft (detergent-resistant membrane) (Gao et al, 2004). Poliovirus infection leads to the appearance of greatly rearranged vesiculated membranes (Suhy et al, 2000), and poliovirus RNA replication occurs on membranes that contain markers of lysosomes, the Golgi apparatus, and the ER (Egger et al, 2000;Schlegel et al, 1996).…”
Section: Involvement Of Membrane Componentsmentioning
confidence: 99%